Science - Penerbitan Pelangi Sdn. Bhd.; Pelangi Multimedia Technologies Sdn. Bhd. (Selangor : Pelangi Multimedia Technologies Sdn. Bhd. : Penerbitan Pelangi Sdn. Bhd. (marketer), 2006)
This cd-rom is throughly developed to assist students in the science subject from form 1 to form 3. It fulfills the syllabus prepared by the Ministry of Education. This cd help students to prepare themselves well in their examinations. A few important tools are featured in the CD
jilid 1. Science form 1 - jilid 2. Science form 2 - jilid 3. Science form 3
System Requirements : Windows 98/ME/2000/XP, processor speed of 800MHz above, multimedia PC spekaer, mouse and keyboard, 256 MB RAM and above
Keywords: Science -- Study and teaching (Secondary); Science -- Problems, exercises, etc